On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Teaching community: A pedagogy of hope. - hooks, bell (Taylor and Francis, 2013)
Il y a dix ans, bell hooks étonnait les lecteurices avec Enseigner à transgresser : l'éducation comme pratique de la liberté . Vient maintenant Communauté d'enseignement : une pédagogie de l'espoir - une œuvre puissante et visionnaire qui enrichira notre enseignement et nos vies. Combinant une réflexion critique sur l'éducation avec des récits autobiographiques, hooks invite les lecteurices à étendre le discours sur la race, le sexe, la classe et la nationalité au-delà de la salle de classe dans des situations d'apprentissage quotidiennes. L'enseignement, explique-t-elle, peut avoir lieu n'importe où, n'importe quand - pas seulement dans les salles de classe des collèges, mais dans les églises, les librairies, les maisons où les gens se réunissent pour partager des idées qui affectent leur vie quotidienne. Dans Teaching Community, bell hooks cherche à théoriser à partir de la place du positif, en regardant ce qui fonctionne. Écrivant sur les luttes pour mettre fin au racisme et à la suprématie blanche, elle fait valoir que "personne ne naît raciste. Tout le monde fait un choix". Communauté d'enseignement nous explique comment nous pouvons choisir de mettre fin au racisme et de créer une communauté bien-aimée. hooks se penche sur de nombreux problèmes, parmi lesquels la spiritualité en classe, les Blancs cherchant à mettre fin au racisme et les relations érotiques entre professeur.e.s et étudiant.e.s. L'esprit, la lutte, le service, l'amour, les idéaux de connaissance partagée et d'apprentissage partagé - ces valeurs motivent un changement social progressif. Les enseignant.e.s visionnaires savent que l'éducation démocratique ne peut jamais se limiter à une salle de classe. L'enseignement - si souvent sous-estimé dans notre société - peut être une activité joyeuse et inclusive. bell hooks montre le chemin. "Lorsque les enseignant.e.s enseignent avec amour, en combinant attention, engagement, connaissances, responsabilité, respect et confiance, nous sommes souvent capables d'entrer dans la classe et d'aller droit au cœur du problème, qui est de savoir quoi faire un jour donné pour créer le meilleur climat d'apprentissage."
Keywords: afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; fem9000; féminisme afroaméricain; inégalités; pédagogie; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

Logiques de genre dans l'enseignement associatif : carrières et pratiques militantes dans des associations revendicatives, 2013 - Rétif, Sophie (Dalloz, 2013)
Thèse pour le doctorat en science politique de l’Institut d’Etudes Politiques de Paris présentée et soutenue sous le titre Genre et engagement associatif. Carrières et pratiques militantes dans six associations françaises et portugaises. Tout espace social où s’organisent des rapports de genre apporte à leur structuration sa contribution propre. Cela veut dire qu’il faut ici prendre au sérieux les idéologies, les croyances comme affectant les anticipations et comportements ouverts aux femmes et hommes au sein des associations. (…) Ici encore, avec ce confort de lecture qui consiste à offrir des analyses stimulantes et bien construites sans les hérisser d’une envahissante signalétique théorique, Sophie Rétif met en oeuvre les fondamentaux d’une analyse de genre intelligente.
Keywords: activisme; approches et analyses; cours; cycles supérieurs; discipline; europe; fem7000; france; idéologie; inégalités; justice sociale; militance; mouvements sociaux; organisations féministes; portugal; rapports de domination; rapports sociaux de sexe; recherche comparative; recherche en milieux de pratique; reproduction sociale; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; travail; étude de cas; étude qualitative

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Tracking Epistemic Violence, Tracking Practices of Silencing - Dotson, Kristie (Hypatia, 2011)
oo often, identifying practices of silencing is a seemingly impossible exercise. Here I claim that attempting to give a conceptual reading of the epistemic violence present when silencing occurs can help distinguish the different ways members of oppressed groups are silenced with respect to testimony. I offer an account of epistemic violence as the failure, owing to pernicious ignorance, of hearers to meet the vulnerabilities of speakers in linguistic exchanges. Ultimately, I illustrate that by focusing on the ways in which hearers fail to meet speaker dependency in a linguistic exchange, efforts can be made to demarcate the different types of silencing people face when attempting to testify from oppressed positions in society.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices épistémiques; inégalités; justice; philosophie; sciences humaines; silenciation; systèmes d'oppressions; thématiques; témoignage; violences; vulnérabilité; éthique

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

Teaching critical thinking: Practical wisdom - hooks, bell (Routledge, 2010)
Dans une série d'essais courts, accessibles et éclairants, hooks explore les sujets déroutants et parfois controversés que les enseignants et les élèves l'ont invitée à aborder depuis la publication des précédents volumes à succès de sa série Teaching, Teaching to Transgress et Teaching Community . . Les questions sont variées et vastes, allant de la question de savoir si un enseignement significatif peut avoir lieu dans une grande salle de classe à la confrontation des problèmes d'estime de soi. Un professeur, par exemple, a demandé comment les professeures noires peuvent maintenir une autorité positive dans une salle de classe sans être vues à travers le prisme de stéréotypes racistes et sexistes négatifs. Un enseignant a demandé comment gérer les larmes en classe, tandis qu'un autre voulait savoir comment utiliser l'humour comme outil d'apprentissage. Abordant les questions de race, de sexe et de classe dans ce travail, hooks discute de l'équilibre complexe qui nous permet d'enseigner, de valoriser et d'apprendre des œuvres écrites par des auteurs racistes et sexistes. Soulignant l'importance de la lecture, elle insiste sur la primauté de la liberté d'expression, une éducation démocratique de l'alphabétisation. Tout au long de ces essais, elle célèbre le pouvoir transformateur de la pensée critique. C'est un travail intellectuel provocateur, puissant et joyeux. C'est une lecture incontournable pour tous ceux qui s'intéressent à l'éducation aujourd'hui.
Keywords: afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; discours dominant; fem9000; féminisme afroaméricain; inégalités; pédagogie; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis